The effect of different Sn-Ag-Cu (SAC) solder form on solder/Cu joint performance through microwave hybrid heating - Maliessa Nabilah, Mazelan (2023)
Solder acts as a joining material in first level packaging such as controlled collapse chipconnection (C4). It helps to interconnect chip with substrate to provide electrical and mechanical continuity in electronic packaging. The quality of electronic packaging mostly relies on the solder joint that makes it a main concern in electronic industry. Previously, reflow soldering process was performed to solder electronic component. Due to its high defect rate, processing time and energy consumption, microwave hybrid heating (MHH) method are getting more attention among electronics manufacturers to perform industrial process as it is beneficial in modern microtechnology. MHH method has faster heating rate, improve heating uniformity, reduces the chance of thermal runaway, reduce processing temperature, and subsequently, reduce hazards to human and environment. This study attempts to investigate the solder joint performance with different form of Sn-Ag-Cu solder through microwave hybrid heating. The soldering parameters were optimized by response surface method (RSM) using Central Composite Design (CCD) method to provide the most suitable soldering parameters to joint SAC305/Cu with MHH method with high shear strength. An investigation of the type of intermetallic compound (IMC) formation and growth were also made. Through this study, samples were joint via MHH and their shear strength was examined using the lap shear test, according to the design of experiment (DOE) generated by CCD. Following the analysis of variance (ANOVA), a mathematical model is built from the response. A mathematical model with quadratic equation was produced and the percentage error for all samples are less than 8%. The optimized parameters include 3-7 g of susceptor with the exposure time of 6-10 minutes. After optimization process, it was found that specimen with 3.05 g SiC and 8.92 minutes for wire solder form possess the highest shear strength with 109.52 MPa, showing increment of 11% compared to the highest shear strength before optimization. For paste solder form, specimen with highest shear strength were obtained with 3.03 g SiC and 9.39 minutes (109.76 MPa) shows increment of 2% compared to the samples before optimization. The microstructure of the IMC was analyzed using optical microscope and the morphology of the shear fracture was analyzed using scanning electron microscopy (SEM). Results showed that there was a high possibility to utilize MHH method in soldering as confirmed by the shear strength results (115.45 MPa for wire solder form and 109.76 MPa for paste solder form) and IMC analysis. Scallop-like Cu6Sn5 IMC were observed at all of the solder/substrate joint and Cu3Sn IMC was found at most of the samples. The IMC thickness depicted an acceptable value for first level packaging (10 um). Hence, microwave hybrid heating shows promising ability to be an alternative in regards to the other soldering technique in electronic industry.